Review of The Artificial Insemination Result Based on Anestrus Post Insemination in Bali Cattle Herds at The Regency of Sikka, East Nusa Tenggara - Tarsisius Considus Topianong; Agung Budiyanto; Erif Maha Nugraha Setyawan (Jurnal Sain Veteriner, 2014)
Anestrus is one of indirect clinical signs of cattle pregnancy. Based on the present of sufficient progesterone on the blood,  the cattle with pregnancy condition will not show the signs of estrus.  The success of artificial insemination (AI) is the occurrence of fertilization followed by pregnancy and parturition. This involves a complex relationship between semen quality and oocytes, estrus detection, AI punctuality, inseminator and farmers ability. Artificial insemination should be performed at the relative optimum time to ovulation. Estrus detection is an important factor to determine the time of AI. Estrus Detection of Bali cattles of the farmer is often difficult observed or not observed, especially in semi-intensive system maintenance. From this review it can be seen that there is the different proportion of inseminators on the incidence of estrus after AI. However, determination of  the role of inseminator on the success of AI and  then the other factors that affect the success of the AI should be under ideal conditions. Straw from the different bulls breed gave the same of AI result. The estimate of pregnancy rate of 80 cows after AI is 55 %.  Estrus detection on 21st days after AI can be used as a detection method for early diagnosis of pregnancy, especially for the  farmers who did not have any ability or authority to perform  medical acts of reproduction which is only owned by a veterinarian. Observation, recording and evaluation of the implementation of the AI should be made until the end of pregnancy  followed by the process of parturition.